Pengaruh Literasi Keuangan, Inklusi Keuangan, dan Financial Technology Terhadap Perilaku Keuangan Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang (Studi Kasus Pengguna BRImo Pada Nasabah Digital Banking) - Muhammad Habibi Rohman Zulkarnaen; Jeni Susyanti; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This research aims to find out how financial literacy, financial inclusion, and financial technology affect the financial behavior of students at the Faculty of Economics and Business, Islamic University of Malang. Data collection was carried out by giving questionnaires to students of the Faculty of Economics and Business, Islamic University of Malang by purposive sampling. Slovin's algorithm is used to calculate the sample size, and the result is 90 respondents. SPSS 25 is used for research data analysis. Validity, reliability, normality, classical assumption test, multiple linear regression test, and hypothesis testing are some of the data testing strategies used in this study. The results show that Financial Literacy has a significant effect on Financial Behavior, Financial Inclusion has no significant effect on Financial Behavior, and Financial Technology has a significant effect on Financial Behavior. Keywords: Financial Literacy, Financial Inclusion, Financial Technology, Financial Behavior